SPACE SYNTAX ANALYSES IN DEFINING THE CONNECTION OF DEVELOPMENT CENTERS IN BALIKPAPAN - Sherlia Sherlia; Nadia Almira Jordan; Elin Dyah Syafitri (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2021)
Old town means an historic or original core of a city which signifies the city’s origin growth. When the city develops and expands its built area, the emergence of a new development center will be inevitable. This study focuses on the connection of the old and new development center of Balikpapan city. In defining the mentioned connection, the authors use Space Syntax theory and depthmapX[net] software to analyze connectivity, integration and choice of the observed networks. Space Syntax analyses helped defining the spatial configuration of the old and the new center of development of Balikpapan city which has higher scores in main connectors and lower scores in local streets which also defines the movement and accessibility of the observed area. It is hoped that this study would be beneficial in guiding the planning and design of the future development of Balikpapan city that is appropriate with its spatial configuration.